Description of Interdependence of Income, Work Time and Farm-Scale of Broiler Kolaka Farms - Doddy Ismunandar Bahari; Reskiati Wiradhika Anwar; Husnaeni Husnaeni (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Will every increase in farming scale decrease the cost per unit of output? Prices for inputs and outputs constantly fluctuate, affecting general livestock production and broiler farming. Consequently, raising livestock farming's efficiency and deciding on its size were in line with the demands of the local economic environment, leading to a rise in livestock revenue. In livestock farming, increasing the farming scale encourages the improvement of livestock infrastructure and the necessary time allocation for farming management. For Farmers, the insights from the findings of this study will provide direction for optimal resource allocation in business development. Furthermore, it helps enrich new insights into the relationship between income, labor time, and scale, especially livestock farming. This study aimed to describe the Interdependence of Income, Characteristics of Working Time, and Farming Scale on broiler farms. This study was conducted in 2023, involving 51 broiler farmers, with farm income, working time, and farm-scale variables as the primary focus. Data analysis was conducted descriptively. The findings indicate that enlarging the scale of broiler farming leads to higher revenue, although necessitating the enlargement of cage space, procurement of more equipment, and the recruitment of additional labor from external sources. The research discovered that expanding the scale of farming leads not only to increased income from broiler farming but also necessitates enlarging the housing area and acquiring additional broiler farming equipment. The available household labor is only adequate to meet the demands of small-scale broiler farming operations. Consequently, at larger scales, farmers rely more on external labor. As a result, the anticipated cost per unit output reduction in broiler farming due to scale expansion does not materialize, as the increased expenditure on additional labor for broiler farming offsets it.